Empowering rural students through digital literacy in English language teaching - Sujariati Sujariati; Herlina Daddi; Risman Wanci (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
Based on the problem rural students often face limited opportunities to develop English proficiency due to restricted access to digital resources, low digital confidence, and teacher-centered instructional practices, this study aimed to explore how integrating digital literacy into English Language Teaching (ELT) can empower rural students by improving their English abilities, particularly in speaking, writing, and communication. The study employed a Classroom Action Research (CAR) design conducted in two cycles of planning, action, observation, and reflection. Participants consisted of one English teacher and approximately twenty students at SMA Negeri 1 Parigi, Gowa. Data were collected through pre- and post-tests, classroom observations, student and teacher interviews, and observation checklists. The findings indicate notable improvements in students’ digital literacy, learner autonomy, creativity, collaboration, and confidence in using English. Digital storytelling and vlogging activities encouraged students to express ideas, practice spoken English, and develop cultural pride, while online collaborative tasks strengthened teamwork and communication skills. Despite challenges such as limited devices, uneven participation, and unstable internet access, students became more engaged and less dependent on teacher guidance over time. Overall, the study demonstrates that context-sensitive digital literacy practices can transform rural ELT classrooms into more participatory, meaningful, and equitable learning environments.